SLOVENSKI FILM V SLIKI, GLASBI IN BESEDI. Ur. Marko Jesenšek: Ljutomer: Gimnazija Franca Miklošiča Ljutomer, 2015. 334 str. - Šek Mertük, Polonca (Slavia Centralis, 2020)
The author presents the scientific monograph Slovene film in image, music and words, which was created on the occasion of the 110th anniversary of the beginning of Slovene film.
Keywords: Slovenski film v sliki, glasbi in besedi; Slovene film in image, music and words; scientific monograph; Marko Jesenšek; review; Slovene film